The land before time IX : journey to big water (Universal City, CA : Universal Pictures, 2002)
When heavy rains create a mysterious "new water", Littlefoot sets off to explore the Great Valley. He quickly becomes friends with Mo, a prank-playing dolphin-like creature who can't find his way back to the Big Water. Littlefoot and his pals come to the rescue and prove the value of courage, friendship, and diversity.